Bmp6 expression in murine liver non parenchymal cells: a mechanism to control their high iron exporter activity and protect hepatocytes from iron overload? - Marco Rausa; Alessia Pagani; Antonella Nai; Alessandro Campanella; Maria Enrica Gilberti; Pietro Apostoli; Clara Camaschella; Laura Silvestri (PLoS ONE, 2015)
Bmp6 is the main activator of hepcidin, the liver hormone that negatively regulates plasma iron influx by degrading the sole iron exporter ferroportin in enterocytes and macrophages. Bmp6 expression is modulated by iron but the molecular mechanisms are unknown. Although hepcidin is expressed almost exclusively by hepatocytes (HCs), Bmp6 is produced also by non-parenchymal cells (NPCs), mainly sinusoidal endothelial cells (LSECs). To investigate the regulation of Bmp6 in HCs and NPCs, liver cells were isolated from adult wild type mice whose diet was modified in iron content in acute or chronic manner and in disease models of iron deficiency (Tmprss6 KO mouse) and overload (Hjv KO mouse). With manipulation of dietary iron in wild-type mice, Bmp6 and Tfr1 expression in both HCs and NPCs was inversely related, as expected. When hepcidin expression is abnormal in murine models of iron overload (Hjv KO mice) and deficiency (Tmprss6 KO mice), Bmp6 expression in NPCs was not related to Tfr1. Despite the low Bmp6 in NPCs from Tmprss6 KO mice, Tfr1 mRNA was also low. Conversely, despite body iron overload and high expression of Bmp6 in NPCs from Hjv KO mice, Tfr1 mRNA and protein were increased. However, in the same cells ferritin L was only slightly increased, but the iron content was not, suggesting that Bmp6 in these cells reflects the high intracellular iron import and export. We propose that NPCs, sensing the iron flux, not only increase hepcidin through Bmp6 with a paracrine mechanism to control systemic iron homeostasis but, controlling hepcidin, they regulate their own ferroportin, inducing iron retention or release and further modulating Bmp6 production in an autocrine manner. This mechanism, that contributes to protect HC from iron loading or deficiency, is lost in disease models of hepcidin production.